Determinants of the Effective Tax Rate: A Study on Food and Beverage Companies - Mochamad Febri Sayidil Umam (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The effective tax rate is intended to measure the portion of a company's actual tax payments relative to its commercial profits. The percentage of effective tax rates for companies has significantly declined due to a reduction in profit levels. This study seeks to examine the influence of Related Party Transactions, Capital Intensity, and Inventory Intensity on the Effective Tax Rate of Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange from 2017 to 2022. The research utilizes quantitative, secondary data sourced from the companies' annual financial reports. The methodology employed includes descriptive and verification analysis. The population consists of Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange during the 2017–2022 period. A purposive sampling technique was used, resulting in a sample of 10 companies, with a total of 60 data points. The study applies the Fixed Effect Model, analyzed using the Eviews 9 software. Data analysis incorporates the classical assumption test, multiple linear regression, determination coefficient analysis, and hypothesis testing through the t-test. The findings reveal that Related Party Transactions have no significant impact on the Effective Tax Rate, Capital Intensity has a significant effect, while Inventory Intensity does not influence the Effective Tax Rate.